Assessing the accessibility of everyday products. - Cardoso, Carlos; Clarkson, P. John; Harrison, Lee-Anne; Langdon, Patrick; Keates, Simeon (2025)
If a product is being designed to be genuinely inclusive, then the designers need to be able to assess the level of exclusion of the product they are working on and identify possible areas of improvement. To be of practical use, the assessments need to be quick, consistent and repeatable. The aim of this workshop is to invite attendees to participate in the evaluation of a number of everyday objects using an assessment technique being considered by the workshop organisers. The objectives include evaluating the effectiveness of the assessment method and to suggest revisions to the assessment scales being used. The assessment technique is to be based on the ONS capability measures (1) which recognises 14 capability scales of which seven are particularly pertinent to product evaluation, namely: motion; dexterity; reach and stretch; vision; hearing; communication; and intellectual functioning. Each of these scales range from 0 (fully able) through 1 (minimal impairment) to 10 (severe impairment). The attendees will be asked to rate the products on these scales. Clearly the assessed accessibility of the product depends on the assumptions made about the context of use. The attendees will be asked to clearly note the assumptions that they are making about the context in which the product is being assessed. The aim is to identify how assessors would use the assessment method in the real world. The objects being assessed will include items such as remote controls, and mobile telephones. The attendees will be asked to assess at least two products. Helpers will be on hand to assist and observe. The assessments will be collated and compared and feedback about the method sought from the attendees. Initial conclusions will be presented at the end of the workshop. More detailed analyses will be made available in subsequent proceedings. Ideal workshop attendance would be between 30 to 40 people.
Include 2001 Conference Book Abstracts from all the papers presented, biographies of the keynote speakers and a full programme of the conference. As given to conference delegates attending (revised edition) Details: A4 portrait, 106pp, illustrated Editor: John Bound, Roger Coleman Designer: Margaret Durkan. Record exists in University of Greenwich repository http://gala.gre.ac.uk/12967/
Keywords: 620 Engineering and allied operations; TA Engineering (General). Civil engineering (General); Assessing Accessibility; Everday Products; Evaluation